2019
DOI: 10.2478/pjct-2019-0018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the composition and fungicidal activity of essential oils from fennel fruits cultivated in Poland and Egypt

Abstract: The yield, composition and fungicidal activity of essential oils obtained from fennel fruits cultivated in Poland (FEOPOL) and Egypt (FEO-EG) were compared. The influence of the duration of hydrodistillation using a Clevenger apparatus on the essential oil yield was studied. The composition of the fennel essential oils was determined by GC-MS method. Studies have shown that FEO-POL and FEO-EG are two distinct chemotypes, which differ in yield and composition. The fennel fruits cultivated in Poland contained 4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Trans-anethole and estragole are the major constituents of the essential oils of different fennel chemotypes. Trans-anethole differs from its isomer estragole in the position of the double bond of prophenyl chain as reported (Gross et al, 2002;Ahmed et al, 2019;Wodnicka et al, 2019). High presence of trans-anethole in our sample clearly reveals that our sample is trans-anethole-rich chemotype of fennel.…”
Section: Chemical Compositions Of Essential Oilssupporting
confidence: 61%
“…Trans-anethole and estragole are the major constituents of the essential oils of different fennel chemotypes. Trans-anethole differs from its isomer estragole in the position of the double bond of prophenyl chain as reported (Gross et al, 2002;Ahmed et al, 2019;Wodnicka et al, 2019). High presence of trans-anethole in our sample clearly reveals that our sample is trans-anethole-rich chemotype of fennel.…”
Section: Chemical Compositions Of Essential Oilssupporting
confidence: 61%
“…The antifungal activity of EOs has been investigated in numerous in vitro studies [32,40,49]. In the present study, in vitro analysis of the linear growth of the fungal species studied showed differences in the antifungal potential of the essential oils investigated.…”
Section: Determination Of Antifungal Activity In Vitromentioning
confidence: 61%
“…The opposite results were obtained by Wodnicka et al [49], who investigated the antifungal properties of dill seed essential oil at a concentration of 10 ppm. The analysed oil reduced the mycelial growth of F. graminearum by 48.8%, of F. avenaceum by 13.3% and of F. culmorum by only 6.2%.…”
Section: Determination Of Antifungal Activity In Vitromentioning
confidence: 77%
See 2 more Smart Citations